Corruption in Electricity Stealing According to Article 2 Paragraph (1) of Law Number 31 of 1999 on Corruption Crime Eradication (Global Journal of Management and Business Research, 2014)
This paper entitled Corruption in Electricity Stealing was intended to answer questions on whether an electricity stealing can be qualified as a corruption crime and to the extent of which electricity stealing crimes may bring about losses in the state's finance. This paper was prepared by a juridicalnormative writing method, that is, by studying legislations contained both in the law itself and in legal literatures/books, particularly those related to stealing and corruption. The result in a juridical aspect form was then written down in a descriptive-analytical way. The conclusion of this paper was the answer to the problems abovementioned as follows: that electricity stealing can be qualified as a corruption crime and that any electricity stealing brings about losses in the state's finance.
Keywords: stealing; electricity; corruption; loss; finance